Effect of Solution Treatment Temperature on Recycled Aluminium Alloy 319 - Murizam Darus; Shamsul Baharin Jamaludin, Assoc. Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.